DEVELOPMENT OF INNOVATIVE POTENTIAL OF MACHINE-BUILDING ENTERPRISES IN CRISIS CONDITIONS: MAIN ASPECTS AND PRACTICAL IMPLEMENTATION - VISHTAK, Inna; PRIAMUKHINA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the strategies of enterprises in various industries for developing the innovative potential of mechanical engineering enterprises. The key aspects of innovative activity in the context of the crisis and the possibilities of its practical implementation in Ukraine are studied. The role of the mechanical engineering industry as a system-forming element of the economy, ensuring technological progress, research potential and competitiveness is determined. The development of innovative activity of mechanical engineering enterprises contributes to the international recognition of domestic products, attracting investment and strengthening positions in the global market. The focus is on the strategic guidelines of the industry, based on the indices of the Global Innovation Rating and the European Innovation Scoreboard. The European integration processes that stimulate the adaptation of enterprises to international markets, the use of state support programs, cooperation with research institutions and the introduction of the latest technologies are taken into account. The main problems of innovative development are identified: lack of funding, imperfect legislation and a low level of innovative potential. Directions for the development of the industry are proposed, including the integration of technologies, cost optimization, the introduction of resource-saving processes and the creation of products that meet international demand. The importance of innovation potential for the competitiveness of mechanical engineering in the context of global challenges is established and ways to increase it for economic growth and post-war recovery are identified.